(untitled) (Journal of Human Sciences, 2018)
The subject of educational supervision is one of the thorny and important subjects in education; because it concentrates on teacher training and accommodates him with the new education ideas, as far as it is the fundamental point in educational operation. And form here it comes this study which is talked about the effect of the educational supervision in the performance of teachers on the professional side and from the opinion of the teachers on the ground themselves. The study content three chapters. Started with the general frame with hold the fundamentals: Introduction, the problem, the importance, the objectives, the questions, the supposals, the program flow-up, the tools used by the researcher in the information analysis to reach the results, the objectivity barriers, spatial and carnal, followed by explanation and illustration of the terms mentioned in the study. The chapter two is the theoretical frame of the study, in which a brief introduction about the educational supervision in Chad, it is different steps, the ways used, the centers who undertake the supervision operation in Chad, the judiciaries contexts for the supervision and also high light the situation of the Chadian supervisors, their missions and their jobs and ended by the last studies. The last chapter is for the practical frame.